Synthesis and Characterization of Lanthanum doped Co-Zn Spinel Ferrites Nanoparticles by Sol-Gel Auto Combustion Method - Gilani , Zaheer Abbas; Farooq, Amir; Asghar, Noor ul Huda Khan; Khalid , Muhammad (Journal of Materials and Physical Sciences, 2020)
Spinel ferrites nanoparticles play a significant role in our everyday lives. In the current work, La3+ doped Co-Zn ferrites with chemical formula Co0.5Zn0.5LaxFe2-xO4 (x = 0.00 to x = 0.2 with step size 0.04) was effectively prepared by sol gel technique. The formation of FCC spinel structure was confirmed by X-Ray diffraction (XRD) analysis. The average crystallite size were calculated to be in the 8 nm to 13 nm range. The lattice parameters were found to be decreased with the doping of lanthanum (La3+) contents. X- Ray density is analyzed to increase as the concentration of (La3+) doping increases, this is due to the fact that La3+ ion has a higher molar weight than Fe3+ ion. The spinel phase structure was affirmed by using FTIR.The two main absorption bands ?1 and ?2 are referred to tetrahedral stretching band and octahedral stretching band respectively, is found to be in the range of at around 400-530 cm-1. Spinel ferrites, such as Co-Zn spinel ferrites, have dielectric features that make them ideal for use in high-frequency applications. With new potential applications being investigated all the time. Physical properties, synthesis method, as well as sintering temperature and time, are all important factors in regulating the properties of dielectric materials. The dielectric features were measured in the frequency of 1 MHz to 3 GHz range. Lowered dielectric parameters studied across a higher frequency range recommend that such nano crystalline ferrites could be used to fabricate the equipment needed to perform at GHz frequencies.